Impoliteness Used in Action Movies - WICAKSONO, Eriek Budi; , Drs. Agus Wijayanto, Ph.D; , Dra. Siti Zuhriyah A., M. Hum (2015)
Pragmatics is the study of meaning that is using non-linguistics knowledge by considering the intentions of the utterance, the context, and the social world. Impoliteness is a communicative strategies with the opposite orientation, that of attacking one's interlocutor and causing disharmony. In simple definition, impoliteness can be interpreted as rudeness. However, Culpeper's suggestion is that impoliteness is intentional while rudeness is unintentional negative behavior. This paper studies the impoliteness strategies used in action movies. This research is a descriptive qualitative method. The data of this research are the excerpts of conversation which are produced by all the characters with containing impoliteness strategy in action movies. The movies are chosen is "Die Hard 3 (1995)" and "The Expendables (2010)". The impoliteness work used by the characters of the movie is analyzed using impoliteness strategies proposed by Culpeper (1996), and it's analyzed again by Kasper theory and Halliday theory (1985) to find out the pragmalinguistic form and the social aspect of contextual meaning in impoliteness strategies founded. The result of the study shows that impoliteness strategy which is used is bald-on record, positive impoliteness, and negative impoliteness that are 94 cases.